The Effect of Dividend Policy as a Moderation Variable on the Effect of Debt Policy and Profitability on Company Value - Neneng Susanti; Sakina Ichsani; Tanti Irawati Muhlis (International Journal of Science and Society, 2023)
This study aims to analyze the effect of dividend policy as a moderating variable on the effect of debt policy and profitability on firm value. This study uses secondary data obtained from the Indonesia Stock Exchange and Finance.yahoo.com. The population in this study are all manufacturing sector companies that have been and are still listed on the Indonesia Stock Exchange for the 2015-2017 period, as many as 141 companies. The sample selection technique uses a purposive sampling method. A sample of 26 manufacturing companies that met the criteria was obtained based on predetermined criteria. The data analysis technique used is hierarchical regression analysis with a moderator variable. Based on the results of data analysis, it can be concluded that (1) Debt policy has a positive effect on firm value; (2) Profitability has a positive and significant effect on firm value; (3) dividend policy moderates the effect of debt policy on firm value; and (4) dividend policy moderates the effect of profitability on firm value.